Energy-Saving Occupant-Feedback Control Method Under Preferred Air-Conditioner Settings of Occupants - Toru Yano; Miho Sako (IEEE Access, 2024)
This study evaluates an occupant-feedback control method under preferred air-conditioner settings of occupants. We performed an experiment where this method was actually used on inverter air-conditioners in multi-occupancy office rooms in Japan in summer and winter for the case where the set-point temperatures of the air-conditioners could be changed freely by occupants. In this experiment, the method estimated acceptable set-point temperatures from data from the previous execution step and applied an energy-saving acceptable set-point temperature to the air-conditioners three times per day for a given period. To evaluate this method, which can be regarded as a nudge, we randomly allocated days where this method was and was not used. To determine the effectiveness of this method, we performed statistical analysis of the set-point temperatures and energy consumption analysis of the air-conditioners. The results showed excessive use of the air-conditioners during days without this method and mitigation of the excessive set-point temperatures by this method. Possible reduction of energy consumption by this method was obtained, whereas some difficulties in the field study, such as uncontrollable usage of meeting rooms, prevented obtaining clear results for the energy-saving by this method. Our findings suggest that a slight change of set-point temperatures may likely lead to energy-saving under preferred HVAC settings of occupants, indicating that statistical analysis of HVAC settings is helpful in confirming the effectiveness of the occupant-feedback control methods under actual HVAC usage.